An integrated framework of reference for the qualification of personnel in coordinate metrology - Savio, Enrico; Menoncin, Marco; Marxer, Michael; Anwer, Nabil; Hausotte, Tino; Bills, Paul; Blunt, Liam (European Society for Precision Engineering and Nanotechnology, Conference Proceedings - 19th International Conference and Exhibition, EUSPEN 2019, 2019)
Advanced measuring equipment, such as Coordinate Measuring Machines, Computed Tomography, Fringe-projection, Photogrammetry, Laser trackers and other systems are essential in manufacturing for both product/process engineering and quality control. Competent personnel are essential to use these systems effectively and efficiently, and their training is a key element of attention in industry. The paper illustrates a proposal for an integrated framework of reference for the qualification of personnel in Coordinate Metrology, having the aim of increasing confidence of employers in qualifications and the recognition of specific competences acquired in different companies and countries. A summary of learning outcomes for Computed Tomography is presented as example.
CRIS-Team Scopus Importer:2019-08-30
Keywords: Coordinate metrology; Qualification of personnel; Reference framework